Implementation Enforcement Embezzlement Of Rental Vehicle Crime In Polsek Banyuurip Satker Polres Purworejo - Tito Dwi Anggoro (Jurnal Daulat Hukum, 2018)
The purpose of this research is to know and analyze the mode of the crime of embezzlement of the car in case Number: BP / 07 / V / 2016 / Criminal in police Banyuurip-Purworejo, to know the investigation on the case, and to know and analyze the obstacles and find solution in the law enforcement process on the perpetrators of criminal fraud in the case of cars Number: B / 145 / V / 2016 / Sek BU Banyuurip Police in Purworejo. This study uses a normative Juridical approach with a specific case study of car embezzlement in Purworejo District. Data collected from case Document Number: BP / 07 / V / 2016 / Criminal then it was Analyzed by using qualitative analysis. The results Showed that the mode of cars embezzlement crime is done by doing the rental activity. That criminal act committed by private employees who rented cars. The reason in using Reviews those cars was for the company's business for two days. The investigation of the case is based on the police report number: LP / B / 09 / V / 2016 / Java / Res Pwr / Sek Bu dated May 2, 2016 about fraud and / or embezzlement. There was no search was done. In the confiscation, some evicences were taken. They were 1 cellphone, 1 BCA book saving, 1 BCA ATM, 1 transaction details at BCA saving, 1 car loan notes, US $ 10,000,000 cash, -, and BPKB guarantee letter from CIMB Niaga bank Yogyakarta.Keywords: Criminal Law Enforcement, Car Rental Embezzlement.